2020
DOI: 10.7759/cureus.8897
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis of Sepsis: A Case Report

Abstract: A 46-year-old man presented with fever, general lethargy, and weight loss over the last few months. He started to develop jaundice and his condition worsened. Blood tests confirmed rising levels of conjugated bilirubin with near-normal alanine aminotransferase, alkaline phosphatase, and prothrombin time. Imaging of the liver and biliary system, including ultrasound, computed tomography (CT), and magnetic resonance cholangiopancreatography (MRCP), did not show any focal lesion or biliary obstruction. Human immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…58 Sepsis may damage sinusoidal perfusion, leading to cholestasis with consequent accumulation of organic anions. 59 Various combinations of changes in liver enzymes and histology are reported to occur in sepsis‐induced cholestasis: (i) high conjugated bilirubin and almost normal ALT, ALP, and prothrombin time 60 ; (ii) increase in total bilirubin, GGT, and ALP, with normal ALT and INR 61 ; (iii) high total bilirubin and ALP with near‐normal ALT and AST 62 ; (iv) liver histological changes and reactive intrahepatic cholestasis. 63 , 64 …”
Section: Methodsmentioning
confidence: 99%
“…58 Sepsis may damage sinusoidal perfusion, leading to cholestasis with consequent accumulation of organic anions. 59 Various combinations of changes in liver enzymes and histology are reported to occur in sepsis‐induced cholestasis: (i) high conjugated bilirubin and almost normal ALT, ALP, and prothrombin time 60 ; (ii) increase in total bilirubin, GGT, and ALP, with normal ALT and INR 61 ; (iii) high total bilirubin and ALP with near‐normal ALT and AST 62 ; (iv) liver histological changes and reactive intrahepatic cholestasis. 63 , 64 …”
Section: Methodsmentioning
confidence: 99%
“…Alterations in the production, transport, and excretion of bile secondary to sepsis can precipitate cholestatic liver disease [ 3 ]. An observational prospective study of 608 patients with sepsis found that only 10.9% were diagnosed with sepsis-associated cholestasis, while 89.1% had sepsis without cholestasis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study found cholestasis was present in 33% of patients with septic shock who had been admitted to an intensive care unit [ 5 ]. Sepsis-related cholestasis often presents with jaundice alongside conjugated hyperbilirubinemia with normal or mildly elevated liver enzymes and alkaline phosphatase (ALP) [ 3 ]. Improvements in jaundice and abnormal lab values often occur alongside sepsis resolution, supporting the notion that these two conditions transpire concurrently.…”
Section: Introductionmentioning
confidence: 99%